2018
DOI: 10.1186/s12872-018-0765-9
|View full text |Cite
|
Sign up to set email alerts
|

The association between oxidative stress and endothelial dysfunction in early childhood patients with Kawasaki disease

Abstract: BackgroundOxidative stress has recently been shown to play an important role in the development of arteriosclerosis in patients with Kawasaki disease (KD); however, no study has investigated this association in early childhood patients with KD. In this study, we evaluated prospectively the association between the levels of oxidative stress and the endothelial function in early childhood patients with KD.MethodsWe compared the derivatives of reactive oxygen metabolites (ROM), flow-mediated dilatation (FMD), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 30 publications
(33 reference statements)
2
30
0
1
Order By: Relevance
“…Oxidative stress serves a key function in the pathophysiology of diseases including hypertension and AS by causing endothelial dysfunction (3). Clinical studies have identified that risk factors leading to AS exert adverse effects on the number and function of endothe-lial progenitor cells, limiting the capability for angiogenesis in patients (4). Oxidative stress has been identified to be associated with the pathogenesis of AS (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress serves a key function in the pathophysiology of diseases including hypertension and AS by causing endothelial dysfunction (3). Clinical studies have identified that risk factors leading to AS exert adverse effects on the number and function of endothe-lial progenitor cells, limiting the capability for angiogenesis in patients (4). Oxidative stress has been identified to be associated with the pathogenesis of AS (4).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have identified that risk factors leading to AS exert adverse effects on the number and function of endothe-lial progenitor cells, limiting the capability for angiogenesis in patients (4). Oxidative stress has been identified to be associated with the pathogenesis of AS (4).…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 demonstrated that seven of the ten most significant GO items were inflammation, immune or stress-related functions, which was consistent with the fact that KD is an acute inflammatory disease. In addition, KD was also characterized with oxidative stress 26,27 . Therefore, iTRAQ gel-free proteomics resulted in a reliable dataset deserving further investigations.…”
Section: Resultsmentioning
confidence: 99%
“…There is an increasing body of evidence that KD involves widespread endothelial dysfunction, such endothelial dysfunction might be induced by reactive oxygen species. It endothelial dysfunction and inflammation in patients with KD is not limited to coronary endothelium but involves renal and mesenteric vascular endothelium and might persist long after resolution of KD [30,31].…”
Section: Endothelial Inflammation In Both Disordersmentioning
confidence: 99%